Pergeseran Penggunaan Bahasa Daerah di Kalangan Generasi Muda - Annisa Maisarah Ulfayanti; Rahmawati Nur Aini (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The shift in the use of local languages among the younger generation has become an increasingly pressing sociolinguistic issue in the context of cultural preservation. This study aims to analyze the factors influencing the decline in local language usage and identify emerging linguistic patterns among youth in urban and semi-urban environments. Using a qualitative descriptive design, data were collected through interviews, observations, and questionnaire surveys involving 75 respondents aged 15–25 years in three major cities in Indonesia. The findings reveal that the shift is primarily driven by modernization, the dominance of Indonesian and foreign languages in digital media, and limited intergenerational transmission within families. Moreover, local languages are increasingly confined to specific cultural or ceremonial contexts, with daily communication dominated by Indonesian and mixed codes. The study concludes that revitalization efforts require collaborative action between families, educational institutions, and cultural organizations. Strengthening local-language-based learning, increasing media exposure, and promoting positive linguistic attitudes are essential strategies to preserve intergenerational language continuity.